Breast cancer survival in the US and Europe: A CONCORD high‐resolution study. Issue 5 (18th September 2012) - Allemani, Claudia; Sant, Milena; Weir, Hannah K.; Richardson, Lisa C.; Baili, Paolo; Storm, Hans; Siesling, Sabine; Torrella‐Ramos, Ana; Voogd, Adri C.; Aareleid, Tiiu; Ardanaz, Eva; Berrino, Franco; et al.
Abstract Breast cancer survival is reportedly higher in the US than in Europe. The first worldwide study (CONCORD) found wide international differences in age‐standardized survival. The aim of this study is to explain these survival differences. Population‐based data on stage at diagnosis, diagnostic procedures, treatment and follow‐up were collected for about 20, 000 women diagnosed with breast cancer aged 15–99 years during 1996–98 in 7 US states and 12 European countries. Age‐standardized net survival and the excess hazard of death up to 5 years after diagnosis were estimated by jurisdiction (registry, country, European region), age and stage with flexible parametric models. Breast cancers were generally less advanced in the US than in Europe. Stage also varied less between US states than between European jurisdictions. Early, node‐negative tumors were more frequent in the US (39%) than in Europe (32%), while locally advanced tumors were twice as frequent in Europe (8%), and metastatic tumors of similar frequency (5–6%). Net survival in Northern, Western and Southern Europe (81–84%) was similar to that in the US (84%), but lower in Eastern Europe (69%). For the first 3 years after diagnosis the mean excess hazard was higher in Eastern Europe than elsewhere: the difference was most marked for women aged 70–99 years, and mainly confined to women with locally advanced or metastatic tumors. Differences in breast cancer survival between Europe and the US in the late 1990s were mainly explained by lower survival in Eastern Europe, where low healthcare expenditure may have constrained the quality of treatment.